2013
DOI: 10.2136/vzj2012.0149
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fate and Transport in a Conventional Onsite Wastewater Treatment System Installed in a Clay Soil: Experimental Results

Abstract: Relationships between N transport and hydraulic function of onsite wastewater treatment systems (OWTSs) in clay‐textured soils are largely unknown. The objectives of this study were to quantify N concentrations in a clay soil and estimate denitrification in the vadose zone beneath a conventional OWTS. An OWTS installed in the Piedmont region of Georgia was dosed with residential strength wastewater three times per day for 2 yr. Soil near trench bottoms cycled between saturated and unsaturated conditions under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 27 publications
9
22
0
Order By: Relevance
“…Mean concentration of TN in the STE (70 mg L −1 ; Table 2) was within the reported values from other conventional OWTS of 47 to 51 mg L −1 (Bradshaw and Radcliffe, 2013a; Siegrist et al, 2014), 43 to 74 mg L −1 in the Wekiva Study area, Florida (Aley et al, 2007), ∼60 mg L −1 ( n = 61) based on a national study (Lowe et al, 2009), 81 mg L −1 (Robertson, 2012), and 26 to 75 mg L −1 (USEPA, 2007). The range of TN (45–80 mg L −1 ) in the STE was also consistent with the literature values of 50 to 90 mg L −1 (Crites and Tchobanoglous, 1998) and 26 to 124 mg L −1 (Lowe et al, 2009).…”
Section: Resultssupporting
confidence: 80%
“…Mean concentration of TN in the STE (70 mg L −1 ; Table 2) was within the reported values from other conventional OWTS of 47 to 51 mg L −1 (Bradshaw and Radcliffe, 2013a; Siegrist et al, 2014), 43 to 74 mg L −1 in the Wekiva Study area, Florida (Aley et al, 2007), ∼60 mg L −1 ( n = 61) based on a national study (Lowe et al, 2009), 81 mg L −1 (Robertson, 2012), and 26 to 75 mg L −1 (USEPA, 2007). The range of TN (45–80 mg L −1 ) in the STE was also consistent with the literature values of 50 to 90 mg L −1 (Crites and Tchobanoglous, 1998) and 26 to 124 mg L −1 (Lowe et al, 2009).…”
Section: Resultssupporting
confidence: 80%
“…The residence time of wastewater in the unsaturated zone will increase with an increase in vadose zone thickness, allowing more time for microbial transformations of nitrogen such as nitrification and denitrification, to occur. Other factors such as the availability of carbon as an electron donor, anaerobic conditions, and availability of NO 3 as an electron acceptor are requirements for NO 3 removal via heterotrophic denitrification and changes in these factors will influence the nitrogen treatment efficiency of OSW. The hydraulic gradient beneath the system was positively correlated with groundwater table elevation ( r = 0.768; p = 0.026) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Groundwater pH beneath the OSW drainfield (4.2 ± 0.5) was significantly lower than in background groundwater away from the system (5.6 ± 0.7) and septic tank effluent (6.4 ± 0.6) (Figure A, Table ). Prior research has also shown that groundwater pH beneath OSW can be one or more pH units lower than wastewater because of the nitrification process beneath the drainfield. Nitrification, the conversion of NH 4 ‐N to NO 3 ‐N via microorganisms, increases the availability of H + , which lowers pH if the soil does not have sufficient buffering capacity or alkalinity .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations